Conventional and microwave assisted synthesis of 2-amino-4,6-diaryl pyrimidine derivatives and their cytotoxic, anti-oxidant activities - Ahmad, Mohammed Rayees; Sastry, Vedula Girija; Prasad, Yejella Rajendra; Khan, Mohammed Haseebur Rahman; Bano, Nasreen; Anwar, Syed (European Journal of Chemistry, 2012)
Pyrimidine is the parent substance of a large group of heterocyclic compounds and plays a vital role in many biological processes. It is also evident from literature; pyrimidines possess potential anti oxidant activities and cytotoxic activities. Chemoprotection by pyrimidines may be a consequence of their antioxidant properties, mediated via inhibition or induction of metabolic enzymes, by an anti-invasive effect or a reduction in nitric oxide production. Free radicals are formed constantly in human system either as accidental products during metabolism or deliberately during the process of phagocytosis; or due to environmental pollutants, ionizing radiations, ozone, heavy metal poisoning, etc. Therefore, it is worthwhile to synthesize some pyrimidine derivatives by conventional and microwave (Catalyst systems) assisted synthesis methods. The synthesized compounds were purified by recrystallization or by chromatography and are characterized by 1H NMR, 13C NMR and IR analysis. The compounds were tested for their potential cytotoxic activity and antioxidant activities by standard methods. The microwave irradiation method (MWI) is proved to be advantageous with considerable increase in the reaction rate with better yields, after over all observation it is found that pyrimidine derivatives possessing cytotoxic and anti-oxidant activities.